Poverty, Allostasis, and Chronic Health Conditions: Health Disparities Across the Lifespan - Val Livingston; Breshell Jackson-Nevels; Erica Brown-Meredith; Alexis Campbell; Brandon D. Mitchell; Candace Riddley; Alicia O. Tetteh; Velur Vedvikash Reddy; Aquila Williams (Encyclopedia)
Poverty is an important social determinant of health disparities across the lifespan. Poverty also influences other life challenges such as pecuniary instability, food insecurity, housing instability, educational inequality, and limited career mobility. According to the World Bank, more than 700 million people worldwide live in global poverty, surviving on less than USD 2.15 a day. Poverty may also be viewed as a state of deprivation that limits access to resources that address basic needs (i.e., food, water, shelter, clothing, health), limiting an individual’s opportunity to participate optimally in society. A large body of research has identified a positive relationship between poverty and chronic health concerns such as heart disease, diabetes, high cholesterol, kidney problems, liver problems, cancer, and hypertension. This entry examines health disparities associated with economic status, discrimination, racism, stress, age, race/ethnicity, gender, gender identity, and nationality from a social justice perspective.